A FT-NIR spectroscopy methodology to estimate firing distance based on the direct analysis of the bullet impact surface. Issue 14 (23rd May 2016) - Sarraguça, Jorge M. G.; Lima, Catarina; Machado, Filipe; Lopes, João A.; Almeida, Agostinho; Fernandes, Luís; Magalhães, Teresa; Santos, Agostinho
Abstract : Fourier transform near-infrared spectroscopy is proposed as a new methodology to estimate firing distance based on the direct analysis of organic components of gunshot residues. Abstract : A new methodology to estimate firing distance based on the direct analysis of organic components of gunshot residues (GSRs) on the bullet impact surface using Fourier transform near-infrared (FT-NIR) spectroscopy is proposed. Mathematical models relating firing distance with spectral information were developed using data obtained from a series of shots performed with a Glock model 17C (114 mm barrel length and 9 × 19 mm cartridges) at different distances, from 20 to 90 cm, against a white 40 × 40 cm square cloth (70% polyester/30% cotton) target. The study was repeated with two different types of ammunition. Spectra were obtained around the bullet entrance hole at 4 perpendicular directions and at 5 radial distances in diffuse reflectance mode with the assistance of a fiber optic probe. Principal component analysis showed that FT-NIRS displayed sensitivity in the recognition of the differences between the GSRs from the two different types of ammunition. Partial least squares regression models allowed the estimation of firing distance for both types of ammunition. Prediction errors lower than 11 cm were obtained for shots up to 90 cm.